Early hemodynamic changes after fetal aortic stenosis valvuloplasty predict biventricular circulation at birth. (26th February 2018) - Prosnitz, Aaron R.; Drogosz, Monika; Marshall, Audrey C.; Wilkins‐Haug, Louise E.; Benson, Carol B.; Sleeper, Lynn A.; Tworetzky, Wayne; Friedman, Kevin G.
Abstract: Objective: To describe the early hemodynamic changes after fetal aortic valvuloplasty (FAV) for evolving hypoplastic left heart syndrome due to mid‐gestational aortic stenosis and to assess whether these early changes predict biventricular (BiV) circulation at neonatal discharge. Method: We retrospectively reviewed all technically successful FAV cases resulting in live birth between 2000 and 2015 ( n  = 93, 45% BiV circulation at neonatal discharge). Paired testing methods were used to compare pre‐intervention and post‐intervention measures of left ventricular hemodynamics. Logistic regression was used to determine whether these changes were predictive of post‐natal outcome. Results: Measures of left heart physiology were markedly abnormal pre‐FAV and improved significantly post‐FAV. No subjects had systolic antegrade transverse aortic arch flow pre‐FAV and 65% of subjects had antegrade flow post‐FAV. The number of subjects with abnormal left‐to‐right patent foramen ovale flow decreased, and the number with biphasic mitral valve inflow increased. The median left ventricular ejection fraction improved after intervention. Amongst the pre‐post changes, gaining partially or exclusively antegrade systolic arch flow was the most significant independent predictor of BiV circulation (OR 9.80 and 19.83, respectively, both P  < 0.001). Conclusion: Technically successful FAV is associated with immediate improvements in left heart physiology that are predictive of BiV circulation at neonatal discharge. Abstract : What's Already Known About This Topic? Mid‐gestational aortic stenosis can progress to hypoplastic left heart syndrome, a condition that is associated with high morbidity and mortality. Fetal aortic valvuloplasty can promote left ventricular growth and function and may prevent progression to hypoplastic left heart syndrome. What Does This Study Add? This study describes for the first time the hemodynamic changes that occur in the first 24 to 48 hours after fetal aortic valvuloplasty. After fetal aortic valvuloplasty, there are significant improvements in fetal hemodynamics, including antegrade systolic transverse aortic arch flow, the direction of FO flow, and left ventricular ejection fraction. We demonstrate that gaining antegrade systolic transverse aortic arch flow increases the odds of post‐natal biventricular circulation.